Crystal structure of (E)-2-[(2S,5R)-2-isopropyl-5-methylcyclohexylidene]hydrazine-1-carbothioamide - Oliveira, Adriano Bof De (2014)
The title compound, C11H21N3S, consists of a menthone moiety attached to an extended thiosemicarbazone group with the N - N - C - N torsion angle being 11.92 (16)°. The cyclohexane ring has a chair conformation and the conformation about the C=N bond is E. In the crystal, molecules are linked via pairs of N - H⋯S hydrogen bonds, forming chains along the a axis. The absolute structure could be assigned with reference to the starting material, i.e. enantiopure (-)-menthone [Flack parameter = 0.05 (5)].